Toxicological and anti-inflammatory effects of lignosus rhinocerotis cooke ryvarden (tiger milk mushroom) / Lee Sook Shien - Lee, Sook Shien (2016)
Lignosus rhinocerotis (Cooke) Ryvarden (Tiger Milk mushroom) has been traditionally used to treat a variety of diseases, including asthma, fever, food poisoning, joint pain, cancers, kidney disorders, body swelling, chronic cough, chronic hepatitis, gastric ulcer and as a general tonic. The sclerotium of the mushroom is the part with medicinal value. This rare mushroom has recently been successfully cultivated, making it possible to be fully exploited for its medicinal and functional benefits. Sub-acute toxicity of the sclerotial powder of L. rhinocerotis from the wild type and two cultivars (termed TM02 and TM03) as well as chronic toxicity of the sclerotial powder of cultivar TM02 were evaluated. There was no treatment-related sub-acute toxicity in rats following 28-days oral administration of 250, 500 and 1000 mg/kg TM02, 1000 mg/kg TM03 as well as 1000 mg/kg wild type L. rhinocerotis sclerotial powder, as measured by haematological, clinical biochemistry, weight, general observations and histological examinations of heart, kidney, spleen, lung and liver. There was also no treatment-related chronic toxicity in rats following the long term (180-days) oral administration of 250, 500 and 1000 mg/kg of L. rhinocerotis (TM02) sclerotial powder, as shown by the clinical observations, body weight gain, haematological analysis, clinical biochemistry, urinalysis, absolute organ weight, relative organ weight and histological examinations of the organs. Thus, the noobserved- adverse-effect level (NOAEL) doses for both sub-acute and chronic toxicity of the respective sclerotial powders were more than 1000 mg/kg. The sclerotial powder of L. rhinocerotis (TM02) at 100 mg/kg did not cause adverse effect on fertility nor teratogenic effect on the offspring of the treated rats. The bacterial reverse mutation assay also showed that the sclerotial powder (TM02) was not mutagenic. Cold water extract (CWE), hot water extract (HWE) and methanol extract (ME) of the sclerotial powder of L. rhinocerotis cultivar TM02 possessed anti-acute inflammatory activity as was iv measured by carrageenan-induced paw oedema test using rats, with CWE having the most potent activity. The acute anti-inflammatory activity of CWE was mainly contributed by its high molecular weight (HMW) fraction isolated by Sephadex G-50 gel filtration chromatography. CWE at 200 mg/kg did not inhibit transudative and proliferative phase of chronic inflammation, as shown by using the cotton pellet induced granuloma in rats. The anti-inflammatory activity of CWE of TM02 which was measured by inhibition of lipopolysaccharide induced TNF-alpha production in RAW 264.7 macrophage cells was mainly contributed by the protein component (also containing carbohydrate) of the HMW fraction as it exhibited strong inhibitory effect on TNF-alpha production with an IC50 of 9.35 ± 0.48 μg/ml based on total carbohydrate and protein content. The protein component was subjected to fractionation by anionic exchange chromatography (Resource™ Q) and two active fractions (F5 and F6) with the strongest inhibitory effect on TNF-alpha production were separated by SDS-PAGE. LC-MS/MS (QTOF) analysis of SDS-PAGE gel section and literature research suggested possible anti-inflammatory candidate(s) of F5 and F6 to be serine proteases (the most potential candidate), lectins and/or immunomodulatory proteins.